Advances in Measurement Systems - Kr Sharma, Milind (IntechOpen, 2010)
This book is a collection of 24 chapters concerning the developments within the Measurement Systems field of study.The collection includes scholarly contributions by various authors and edited by a group of experts pertinent to Measurement Systems. Each contribution comes as a separate chapter complete in itself but directly related to the book's topics and objectives. The target audience comprises scholars and specialists in the field.